2015
DOI: 10.1017/jfm.2015.281
|View full text |Cite
|
Sign up to set email alerts
|

Triple-deck and direct numerical simulation analyses of high-speed subsonic flows past a roughness element

Abstract: This paper is concerned with the boundary-layer separation in subsonic and transonic flows caused by a two-dimensional isolated wall roughness. The process of the separation is analysed by means of two approaches: the direct numerical simulation (DNS) of the flow using the Navier-Stokes equations, and the numerical solution of the triple-deck equations. Since the triple-deck theory relies on the assumption that the Reynolds number (Re) is large, we performed the Navier-Stokes calculations at Re = 4 × 10 5 base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
1
9
0
1
Order By: Relevance
“…However, with the increase in computing power, LES is becoming a feasible technique to underpin the complexity of challenging industrial flows at high-Reynolds numbers, and spectral element methods (also referred to as spectral/hp methods, briefly SEM) are a competitive candidate to improve the performance of the overall computer-aided workflow [45]. In fact, the adoption of SEM in the context of LES, including the use of continuous Galerkin (CG) methods [28,30], standard discontinuous Galerkin (DG) methods [5,21,22,35,47,57,69,73], hybridized DG methods [16,17], spectral difference (SD) methods [33,54] and flux reconstruction (FR) methods [53,70], is emerging as a promising approach to solve complex turbulent flows. First, they allow for high-order discretizations on complex geometries and unstructured meshes.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the increase in computing power, LES is becoming a feasible technique to underpin the complexity of challenging industrial flows at high-Reynolds numbers, and spectral element methods (also referred to as spectral/hp methods, briefly SEM) are a competitive candidate to improve the performance of the overall computer-aided workflow [45]. In fact, the adoption of SEM in the context of LES, including the use of continuous Galerkin (CG) methods [28,30], standard discontinuous Galerkin (DG) methods [5,21,22,35,47,57,69,73], hybridized DG methods [16,17], spectral difference (SD) methods [33,54] and flux reconstruction (FR) methods [53,70], is emerging as a promising approach to solve complex turbulent flows. First, they allow for high-order discretizations on complex geometries and unstructured meshes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, comparisons with experiments (Wu 2001a, b) indicate that the theory, especially with the extension to second-order accuracy, predicts fairly accurately receptivity in the incompressible regime. Recent DNS studies (Mengaldo et al 2015, De Tullio & Ruban 2015 showed that the same is true for subsonic boundary layers. Nevertheless, further work is still needed in order to validate the present theoretical results for supersonic boundary layers.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, it is a good approximation of the skin temperature close to the leading edge of civil aircraft at similar altitudes and speeds. In addition, this choice permitted a direct comparison of the results with those obtained for the equivalent two-dimensional simulations in [31,32]. The Prandtl number Pr, defined as the ratio of kinematic viscosity ν to thermal diffusivity α = k/ρC p , that is, Pr = C p μ/k, where C p is the specific heat at constant pressure, was fixed and corresponds to the value commonly adopted for air.…”
Section: Problem Formulationmentioning
confidence: 99%
“…The computational domain is a Cartesian box extending for L x ≈ 40δ, L y ≈ 20δ, and L z ≈ 6δ in the streamwise (x), spanwise (y), and normal (z) directions, where δ is the compressible boundarylayer thickness at the roughness location at Ma = 0.87 chosen as the reference length of the domain. The size of the domain in the streamwise direction was based on a sensitivity study performed in [31] for a similar two-dimensional problem. The size of the domain in the spanwise direction was based on considerations of the dimensions of flow structures behind the hump.…”
Section: A the Dns Domain And Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation